Successful Treatment of Cutaneous Curvularia geniculata, Nocardia niigatensis, and Viral Papillomatosis in a Dog During the Therapeutic Management of Immune-Mediated Hemolytic Anemia - Strzok, Emily; Siepker, Chris; Armwood, Abigail; Howerth, Elizabeth; Smith, Joanne; Banovic, Frane (Frontiers in Veterinary Science, 2019)
Opportunistic infections represent a major cause of mortality in immunocompromised patients. Discontinuation or reduction of immunosuppressive medications is recommended with the development of opportunistic infections, which may cause a relapse or worsening of the immune-mediated disease. A 7.5-year-old, spayed female Great Dane was diagnosed with immune-mediated hemolytic anemia with initial immunosuppressive therapy consisting of oral prednisone, ciclosporin and mycophenolate mofetil. The patient developed diffuse right forelimb pyogranulomatous fungal dermatitis with deep draining tracts 6 weeks into immunosuppressive treatment with Curvularia geniculata growth. Oral once daily terbinafine and itraconazole were initiated; ciclosporin was immediately discontinued and the mycophenolate mofetil/prednisone administration frequency was reduced. The right forelimb skin lesions resolved after 4 weeks, but the patient presented with a diffuse severe neutrophilic dermatitis on the left forelimb; 16S rRNA sequencing identified Nocardia niigatensis. Cutaneous nocardiosis was treated with oral enrofloxacin and doxycycline; systemic immunosuppressives were continued for immune-mediated hemolytic anemia control. One month later, the left forelimb lesions completely resolved but the patient developed several multifocal, exophytic warts; the clinical features and histopathology was consistent with viral papillomas. Within the following 4 weeks, the patient developed severe diffuse papillomatosis of the left forelimb which was successfully treated with every other day topical imiquimod administration. In this case, successful treatment of cutaneous opportunistic bacterial, fungal and viral infection was possible with proper treatment even though the immunosuppressive drug treatments could not be discontinued.